Sosialisasi Pentingnya Keluarga Berencana dalam Meningkatkan Pengetahuan Pemilihan Alat Kontrasepsi pada Wanita di Desa Blang Pala Kecamatan Banda Baro Kabupaten Aceh Utara - Dian Rahayu; Sri Zulfa Maisih; Sapriani Rahayu; Kiki Asrifa Dinen (Lembaga Pengembangan Kinerja Dosen, 2025)
One of the important problems faced by developing countries, such as Indonesia, is the population explosion. The population explosion results in a rapid population growth rate. To overcome this problem, the Indonesian government has implemented a Family Planning (KB) program that began in 1968. The family planning program provides an opportunity to regulate birth spacing or reduce the number of births by using hormonal or non-hormonal contraceptive methods. Based on data collection that has been carried out in Blang Pala, Banda Baro District, North Aceh Regency, this Community Service activity is to maximize maternal and child health services in the hope of reducing the rate of population growth. This Community Service activity was carried out by providing information about KB and KB Services in Blang Pala, Banda Baro District, North Aceh Regency, totaling 15 people. The results of this KB Service activity were continued by providing an evaluation to acceptors, namely Questions and Answers about KB and knowledge of choosing contraceptives. KB participants were able to answer and explain the questions asked well. The results of the activity showed an increase in knowledge before and after the activity was carried out. It can be concluded that community service activities in the form of counseling and KB Services have a very good impact on those in the local area and can increase the coverage of MKJP